Role of inflammation and cytokines in peripheral nerve regeneration - Dubový, Petr; Jančálek, Radim; Kubek, Tomas (International review of neurobiology, 2013)
This chapter provides a review of immune reactions involved in classic as well as alternative methods of peripheral nerve regeneration, and mainly with a view to understanding their beneficial effects. Axonal degeneration distal to nerve damage triggers a cascade of inflammatory events alongside injured nerve fibers known as Wallerian degeneration (WD). The early inflammatory reactions of WD comprise the complement system, arachidonic acid metabolites, and inflammatory mediators that are related to myelin fragmentation and activation of Schwann cells. Fine-tuned upregulation of the cytokine/chemokine network by Schwann cells activates resident and hematogenous macrophages to complete the clearance of axonal and myelin debris and stimulate regrowth of axonal sprouts. In addition to local effects, immune reactions of neuronal bodies and glial cells are also implicated in the survival and conditioning of neurons to regenerate severed nerves. Understanding of the cellular and molecular interactions between the immune system and peripheral nerve injury opens new possibilities for targeting inflammatory mediators to improve functional reinnervation.
Keywords: Animals; zánět; Cytokines; Axonal regeneration; Inflammatory mediators; cytokiny; lidé; Peripheral Nerves; Peripheral Nerve Injuries; Wallerian degeneration; signální transdukce; Wallerian Degeneration; Signal Transduction; poranění periferního nervu; Inflammation; regenerace nervu; Nerve Regeneration; Immune cells; periferní nervy; Wallerova degenerace; Neuroinflammation; zvířata; Humans